2015
DOI: 10.1128/aac.04347-14
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inhibitor of Gyrase B Is a Potent Drug Candidate for Treatment of Tuberculosis and Nontuberculosis Mycobacterial Infections

Abstract: dNew drugs to treat drug-resistant tuberculosis are urgently needed. Extensively drug-resistant and probably the totally drugresistant tuberculosis strains are resistant to fluoroquinolones like moxifloxacin, which target gyrase A, and most people infected with these strains die within a year. In this study, we found that a novel aminobenzimidazole, VXc-486, which targets gyrase B, potently inhibits multiple drug-sensitive isolates and drug-resistant isolates of Mycobacterium tuberculosis in vitro (MICs of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 33 publications
3
101
2
Order By: Relevance
“…The relationship between acquired moxifloxacin resistance and the moxifloxacin AUC/MIC was best described by a quadratic function, similar to our findings with M. tuberculosis (25). However, the underlying mechanism for moxifloxacin resistance in M. abscessus deserves further exploration; DNA gyrase is still an interesting bacterial target against which new inhibitors are being developed, with evaluation of their potential for use against M. abscessus and other nontuberculous mycobacteria (42).…”
Section: Discussionsupporting
confidence: 69%
“…The relationship between acquired moxifloxacin resistance and the moxifloxacin AUC/MIC was best described by a quadratic function, similar to our findings with M. tuberculosis (25). However, the underlying mechanism for moxifloxacin resistance in M. abscessus deserves further exploration; DNA gyrase is still an interesting bacterial target against which new inhibitors are being developed, with evaluation of their potential for use against M. abscessus and other nontuberculous mycobacteria (42).…”
Section: Discussionsupporting
confidence: 69%
“…Studies using multiple animal models have shown that bedaquiline is efficacious against M. tuberculosis, Mycobacterium leprae, and to some extent M. avium (25,(35)(36)(37). Bedaquiline potently inhibits the mycobacterial enzyme complex ATP synthase, thus interfering with energy production and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 14. The two subclasses of benzimidazole ureas, with their optimal properties for reduced serum shift [78][79][80].…”
Section: Inhibitors Focused On Mycobacterium Tuberculosis Dna Gyrasementioning
confidence: 99%